Physical Self-concept in Mexican Adolescent men and women - Judith Margarita Rodríguez Villalobos; Humberto Blanco Vega; Susana Ivonne Aguirre Vásquez; José René Blanco Ornelas; Ana Citlalli Díaz Leal; Elia Verónica Benavides Pando; Perla Jannet Jurado García (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of the present study was to compare the profiles of physical self-concept between men and women primary and secondary Mexican school students. A total sample of 1146 participants, 550 women and 596 men, aged 11-16 years participated in this study. A quantitative approach with a descriptive and transversal survey design was used. All the participants completed the Physical Self-Description Questionnaire. The results of the one-way multivariate analysis of variance, followed by the one-way univariate analyses of variance, showed that compared with the women, the men obtained higher scores on the subscales health, coordination, activity, sports competence, strength, flexibility, endurance and global physical self-concept. However, in the body fat, appearance and global self-esteem subscales statistically significant differences were not found. Because of the differences between men and women in their perception of physical self-concept found, these findings suggest that in order to design any intervention for improving the perceived physical self-concept of the students, the variable sex should be taken into account.